The Influence of Brand Trust and Brand Image on Consumer Decisions in Purchasing Coffee Beans at Koloni Coffee Palembang - Muhammad Haekal Apriansyah; Roswaty Roswaty; Mohammad Kurniawan (ProBisnis : Jurnal Manajemen, 2023)
In the current era, technological advances are increasing quite rapidly. The increase in technology is due to modernization and globalization that occurs. The purpose of this study was to analyze the effect of brand trust and brand image on consumer decisions in purchasing coffee beans at Koloni Coffee Palembang. This research uses field research (field reaserch) with a descriptive approach. Data collection techniques using questionnaires, observations, interviews, and documentation. the population taken is buyers of coffee beans at Koloni Coffee both directly and indirectly in a month consumers reach 50 customers. this study uses independent variables and dependent variables. The results of the study using the Partial test on the Brand Trust variable obtained a t-count value of 3.780> 2.012, and a significance level <0.05 (0.00 <0.05). So it can be concluded that the Brand Trust variable has a positive and significant effect on consumer decisions in purchasing coffee beans at Koloni Kopi.